Advocacy for Business Protection: The Role of Business Identification Numbers in Safeguarding Business Actors - Fibrianti, Nurul; Maharani, Chatila; Sari, Maylia Pramono; Paramita, Niken Diah; Viana, Anisa Okta; Putra, Tegar Islami (Indonesian Journal of Advocacy and Legal Services, 2024)
The provision of a Business Identification Number (NIB) is an important thing for business actors. One of the benefits of the issuance of NIB for business actors is that the government can provide assistance by means of technical guidance, consultation, and training to increase knowledge of the application of Indonesian national standards and halal product guarantee certification, and so on. However, today, there are still many business actors who do not know how the benefits of NIB for business actors, especially the role of NIB in protecting business actors. This article aims to find out how the role of the Business Identification Number in protecting business actors in Indonesia. This study uses normative juridical research method. The results showed that there are several roles of the Business Identification Number in protecting business actors. Business actors get legal protection in carrying out business operations. In addition, NIB also functions as a legal identity for business actors, which allows them to obtain valid business licenses, commercial licenses, and operations. In addition, NIB makes it easier for businesses to apply for business licenses and fulfill legality requirements. NIB can also increase the competitiveness of business actors by fulfilling the requirements to obtain certification. The issuance of NIB for business actors can be a form of contribution to the development of a better business ecosystem.